Introduction to Docker CI/CD (O'Reilly Media, Inc., 2022)
Containers are often advertised as solving a multitude of problems relating to delivering and maintaining highly available software in the always-on, global environment that most organizations must serve today, but how can they actually help you? What problems are you actually experiencing that can be solved with containers and its closely related technologies? After becoming comfortable with using containers in your day-to-day development workflow, the next step is to take containers deeper into your DevOps pipeline. In this class, we will use Docker Compose to help us set up a fully functioning containerized CI/CD pipeline on our local development systems. The resulting setup will allow each student to write some code, check that code into a git repo, and then watch that code get automatically built, tested, and potentially deployed, using containers for everything.